2020
DOI: 10.1080/1331677x.2019.1706602
|View full text |Cite
|
Sign up to set email alerts
|

Motivation of the youth of Bosnia and Herzegovina to start a business: Examining aspects of education and social and political engagement

Abstract: In the present study, several logit models were tested to identify the antecedents of entrepreneurial intention among the youth of Bosnia and Herzegovina (B&H). Specifically, we explore whether demographic and socio-economic characteristic or whether perceptions of education curriculum and social and political engagement as well as the perception of media influence have an impact on the intention to start one's own business. Data analysis was done on a sample of 3,611 young people. Education level and percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(77 reference statements)
2
2
0
Order By: Relevance
“…Some other reasons refer to the self-confidence of people at that level of age which is higher than people who are over 65. These findings are consistence with the study done by Turulja, Agic, and Veselinovic (2020) which found that age positively affects entrepreneurial intention.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Some other reasons refer to the self-confidence of people at that level of age which is higher than people who are over 65. These findings are consistence with the study done by Turulja, Agic, and Veselinovic (2020) which found that age positively affects entrepreneurial intention.…”
Section: Discussionsupporting
confidence: 90%
“…A series of recent studies have indicated that there is an influence between age and intention, and it was found that age positively relates to entrepreneurial intention. This finding confirms that a person's entrepreneurial intent grows with age (Turulja, Agic, & Veselinovic, 2020;Schwarz et al 2009). In addition, previous studies confirm that age is associated with a lower likelihood of having an entrepreneurial intention (Nguyen, 2018;Hatak et al, 2015).…”
Section: Literature Review Agesupporting
confidence: 77%
See 2 more Smart Citations
“…The author argues that business barriers can be demotivational toward engagement in entrepreneurship. Turulja et al (2020) defined business barriers as the total of the legal and institutional barriers, market barriers, financial barriers, and entrepreneurial infrastructure, among other things. He mentioned that different environments influence motivation and barriers can decrease the motivation to be involved in start-ups.…”
Section: Introduction 1research Background and Problem Statementmentioning
confidence: 99%